2010
DOI: 10.1007/s11426-010-4109-6
|View full text |Cite
|
Sign up to set email alerts
|

Size and support effects for CO oxidation on supported Pd catalysts

Abstract: Supporting Pd catalysts characterized significant different size distribution were obtained using PdCl2, [Pd(NH3)(4)](NO3)(2) and Pd(acac)(2) as precursors. High-resolution transmission electron microscopy (TEM), X-ray diffraction (XRD), in-situ Fourier transform infrared spectroscopy (FTIR) and Raman spectroscopy were used to examine the dispersion of Pd. Catalytic performance measurements show that the activities for CO oxidation increase as the Pd particle size decreases and the O-2/CO ratio increases. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 39 publications
5
14
0
Order By: Relevance
“…Contrary to CH 4 , CO oxidation activity of 2Pd/YFO, 0.5Pd/YFO and Pd/ACZ decreases upon ageing (Table 2) and the structural changes produced by thermal ageing appear more severe likely as a result of Pd particle growth. 82,83 This is in agreement with observations on Pd-based catalysts aged on a dynamometer. 84 Besides, the YFeO 3 support alone exhibited deactivation upon consecutive reaction runs.…”
Section: Three-way Catalytic Activitysupporting
confidence: 90%
“…Contrary to CH 4 , CO oxidation activity of 2Pd/YFO, 0.5Pd/YFO and Pd/ACZ decreases upon ageing (Table 2) and the structural changes produced by thermal ageing appear more severe likely as a result of Pd particle growth. 82,83 This is in agreement with observations on Pd-based catalysts aged on a dynamometer. 84 Besides, the YFeO 3 support alone exhibited deactivation upon consecutive reaction runs.…”
Section: Three-way Catalytic Activitysupporting
confidence: 90%
“…Catalytic CO oxidation on platinum group metals is of great interest for fundamental research [1][2][3][4], and has been known to exhibit nonlinear phenomena such as hysteresis and bifurcation. Elucidation of the nonlinear mechanisms is important for catalyst design and control of reaction routes.…”
Section: Background and Previous Workmentioning
confidence: 99%
“…Thus, the high activity of Ru might contribute to its interaction with the FeO x support. Actually, the support effects for CO oxidation have been examined experimentally . For example, Ito et al .…”
Section: Introductionmentioning
confidence: 99%
“…Actually,t he support effects for CO oxidation have been examined experimentally. [32][33][34][35][36][37][38][39][40] For example, Ito et al [34] revealed that the activity of Rh-based catalysts for the CO preferentialo xidation reactionf ollows the order: Rh/Nb 2 O 5 > Nb 2 O 5 -Rh/SiO 2 > Rh/SiO 2 > RhNbO 4 /SiO 2 .L ie tal. [35] prepared various supported platinum catalysts (Pt/MeO x ,M e= Fe, Zn, Al, Ni)b yc olloid depositioning, and found that Pt/Fe 2 O 3 shows unusual low-temperaturea ctivity and long-term stability.M oreover,o xide-supported Ru catalysts with different substrates have been synthesized, such as g-Al 2 O 3 [41][42][43] and TiO 2 , [44] and are well known for their high activity for CO oxidation at high temperature (100-400 8C), [45][46][47][48] but have al ow activity at 80 8C.…”
Section: Introductionmentioning
confidence: 99%